Features of methodological principles of formation land use of defense - Tretyak А.; Melnychuk, A. (Land Management, Cadastre and Land Monitoring, 2020)
The expediency of reviewing the bases of the classification of land in the category of defense substantiated. The classification of the land use of defense according to the degree of ecological and economic risk is determined. A logical and meaningful model of the methodological process of allocation of defense lands by types (subtypes), target and functional use is proposed. Land allocation should base on clearly defined target criteria, parameters and characteristics, the system of which determined by a specific subject area and the requirements of specific groups of land users.However, land redistribution must done according to the needs and interests of the people (society). After all, the earth, as a natural resource, depending on the value and availability of certain natural resources, performs the following functions [8]: the basis of human life, the source of satisfaction of its primary needs, the most important condition for the existence of changing human generations; • the basis of all existing biocenoses and the biosphere as a whole; • the main source of the aesthetic beauty and richness of the whole natural complex as a whole. In this regard, land use of defense must be classified by special and other modes of use and protection of land and other natural resources, by subtypes: - land use with a low degree of environmental and economic risk; - land use with significant environmental and economic risk; - land use with increased ecological and economic risk; - land use with catastrophic degree of ecological and economic risk. Using the concept of the nature of land allocation for defense and security purposes it is possible to formulate its concept. Allocation of land for defense and security purposes - is a process of land allocation taking into account the needs of the state’s defense capability, as its ability to protect in the event of armed aggression or armed conflict aimed at satisfying the state’s public interest in defense and security needs, with appropriate functional zone use and protection of land and other natural resources (by sub-types of land use) taking into account different degrees of ecological and economic risk. The implementation of a scientifically grounded distribution of land by types (subtypes) of land use, purpose and functional use is one of the functions of the state for the implementation of land policy in the field of defense. Thus, the essence of land allocation lies in balancing contradictions in the needs of the state’s land for defense and security purposes and the availability (possibility of allocating zones of subtypes of land use) land and other natural resources of an appropriate amount and regime of land use. Keywords. Land use of defense, land categories, types of land use, land use regime.